Urgensi Keterampilan Komunikasi Nonverbal Guru Pada Era Society 5.0 - Aida Ambarawati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
Welcoming society 5.0 in education, of course, will face various complexities. One of them is related to the abilities and skills of the teacher. The skills in question are teacher communication skills, teacher communication is a requirement for teaching and learning activities that lead to educational goals and will have an impact on the quality of human resources produced. This research uses library research, in which data collection techniques are carried out by exploring data obtained from various sources of scientific work. This article aims to describe and explain the urgency of teacher nonverbal communication skills in the era of society 5.0. The results of this study, shows that teacher communication skills are one of the crucial things in education in the era of society 5.0. Culture is one of the components that influence meaning in nonverbal communication. In addition, teacher nonverbal communication is a component that affects the teaching and learning process, learning attractiveness, and the quality of student learning outcomes.